2021
DOI: 10.1002/anie.202015004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonding Assisted Catalytic Kinetic Resolution of Acyclic β‐Hydroxy Amides

Abstract: Enantioenriched acyclic a-substituted b-hydroxy amides are valuable compounds in chemical, material and medicinal sciences, but their enantioselective synthesis remains challenging. A catalytic kinetic resolution (KR) of such amides with selectivity factor(s) up to > 200 is developed via enantioselective acylation of primary alcohol with N-heterocyclic carbene. An enhanced selectivity for the catalytic KR process is realized using cyclic tertiary amine as base additive. Diastereomeric transition state models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Molecular sieves (MSs) have been shown to perform an essential role in many NHC-catalyzed asymmetric reactions. 33 Gratifyingly, with 10 mg of a 4 Å MS as an additive, the amidation of lactam was achieved and provided the product (3 S ,4′ R ,5′ R )- 3aa with 96% ee and the recovered (3 R ,4′ S ,5′ S )- 1a with 90% ee, with an S -factor of 245 (Table 1, entry 13). In addition, investigation of the amount of DBU used indicated that increasing it could preserve a comparatively favorable enantioselective performance, whereas reducing it provided a rather inferior result (see ESI Table S1,† and Table 1, entries 9 and 10).…”
Section: Reaction Optimizationmentioning
confidence: 99%
“…Molecular sieves (MSs) have been shown to perform an essential role in many NHC-catalyzed asymmetric reactions. 33 Gratifyingly, with 10 mg of a 4 Å MS as an additive, the amidation of lactam was achieved and provided the product (3 S ,4′ R ,5′ R )- 3aa with 96% ee and the recovered (3 R ,4′ S ,5′ S )- 1a with 90% ee, with an S -factor of 245 (Table 1, entry 13). In addition, investigation of the amount of DBU used indicated that increasing it could preserve a comparatively favorable enantioselective performance, whereas reducing it provided a rather inferior result (see ESI Table S1,† and Table 1, entries 9 and 10).…”
Section: Reaction Optimizationmentioning
confidence: 99%
“…Enantioenriched acyclic α-substituted β-hydroxy amides are valuable pharmacophores and versatile precursors to enantioenriched 1,3-diols, 1,3-amino-alcohols, β-hydroxy acids and β-amino acids, but their enantioselective synthesis remains challenging. Recently, Guin et al [18] realized the kinetic resolution of acyclic α-substituted β-hydroxy amides utilizing enantioselective acylation of primary alcohol via oxidative NHC catalysis (Scheme 12). The selectivity factor (s) was up to >200.…”
Section: Kinetic Resolutions Mediated By Acyl Azoliumsmentioning
confidence: 99%
“…Our group is interested in developing new asymmetric organic transformations with NHC-catalysis. 8 Following our recent study 9 and the literature, 10 we envisaged that the intramolecular hydrogen bonding between diols of achiral 3,3′-bis(hydroxymethyl)oxindoles may lead to a less flexible spiro-cyclic structure, which would ease the selective esterification of one of the alcohols of the substrate by the in situ formed chiral acyl azolium intermediate (Scheme 1b).…”
mentioning
confidence: 99%